First European Haplotype of Echinococcus multilocularis Identified in the United States: An Emerging Disease?. (21st March 2020) - Polish, Louis B; Pritt, Bobbi; Barth, Thomas F E; Gottstein, Bruno; O'Connell, Elise M; Gibson, Pamela C
Abstract: Background: Echinococcus multilocularis is one of the most severe and lethal parasitic diseases of humans, most often reported in Europe and Asia. Only 1 previous case has been documented in the contiguous United States from Minnesota in 1977. European haplotypes have been identified in carnivores and domestic dogs as well as recently in patients in western and central Canada. Methods: We used immunohistochemical testing with the monoclonal antibody Em2G11 and a species-specific enzyme-linked immunosorbent assay affinity-purified antigen Em2, as well as COX1 gene sequencing. Results: Using pathology, immunohistochemical staining, specific immunodiagnostic testing, and COX1 gene sequencing, we were able to definitively identify E. multilocularis as the causative agent of our patient's liver and lung lesions, which clustered most closely with the European haplotype. Conclusions: We have identified the first case of a European haplotype E. multilocularis in the United States and the first case of this parasitic infection east of the Mississippi River. Given the identification of this haplotype in Canada, this appears to be an emerging infectious disease in North America. Abstract : We have identified the first case of a European haplotype Echinococcus multilocularis in the United States. Given the recent identification of this haplotype in Canada, this may be an emerging infectious disease in North America.